Mechanisms of Virus-Induced Airway Immunity Dysfunction in the Pathogenesis of COPD Disease, Progression, and Exacerbation - Guo-Parke, Hong; Linden, Dermot; Weldon, Sinéad; Kidney, Joseph C.; Taggart, Clifford C. (Frontiers in Immunology, 2020)
Chronic obstructive pulmonary disease (COPD) is the integrated form of chronic obstructive bronchitis and pulmonary emphysema, characterized by persistent small airway inflammation and progressive irreversible airflow limitation. COPD is characterised by acute pulmonary exacerbations and associated accelerated lung function decline, hospitalisation, readmission and an increased risk of mortality, leading to huge social-economic burdens. Recent evidence suggests approximately 50% of COPD acute exacerbations are connected with a range of respiratory viral infections. Nevertheless, respiratory viral infections have been linked to the severity and frequency of exacerbations and virus-induced secondary bacterial infections often result in a synergistic decline of lung function and longer hospitalization. Here, we review current advances in understanding the cellular and molecular mechanisms underlying the pathogenesis of COPD and the increased susceptibility to virus-induced exacerbations and associated immune dysfunction in patients with COPD. The multiple immune regulators and inflammatory signalling pathways known to be involved in host-virus responses are discussed. As respiratory viruses primarily target airway epithelial cells, virus-induced inflammatory responses in airway epithelium are of particular focus. Targeting virus-induced inflammatory pathways in airway epithelial cells such as Toll like receptors (TLRs), interferons, inflammasomes or direct blockade of virus entry and replication may represent attractive future therapeutic targets with improved efficacy. Elucidation of the cellular and molecular mechanisms of virus infections in COPD pathogenesis will undoubtedly facilitate the development of these potential novel therapies that may attenuate the relentless progression of this heterogeneous and complex disease and reduce morbidity and mortality.